2012
DOI: 10.1080/13675567.2012.709836
|View full text |Cite
|
Sign up to set email alerts
|

Organisation of multilateral LTL alliances

Abstract: In the less-than-truckload (LTL) market, alliances of smaller logistics service providers successfully compete with large, integrated logistics corporations. However, such alliances are often seen as an inferior governance mode in terms of establishing and operating cost-efficient production structures. Because little is known about the organisation of such multilateral LTL alliances, this paper conceptualises and explores their cooperative organisation and offers tentative explanations for their specific orga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 22 publications
(19 reference statements)
0
11
0
Order By: Relevance
“…To overcome the latter, some organisational concepts have been proposed. For carrier collaboration (S2 for example), a limited liability company (LLC) is usually formed to organise and manage an alliance (or a coalition) (Albers and Klaas-Wissing 2012). LLC can be economically independent (owned by someone outside the alliance) or dependent (owned by the partners in the alliance).…”
Section: Organisation (I6)mentioning
confidence: 99%
“…To overcome the latter, some organisational concepts have been proposed. For carrier collaboration (S2 for example), a limited liability company (LLC) is usually formed to organise and manage an alliance (or a coalition) (Albers and Klaas-Wissing 2012). LLC can be economically independent (owned by someone outside the alliance) or dependent (owned by the partners in the alliance).…”
Section: Organisation (I6)mentioning
confidence: 99%
“…Business certainly is not static; you cannot assume relationships will be either" (Daugherty, 2011: 24). However, the logistics industry is dynamic, with some alliances operating for more than a decade and others collapsing even before they begin operations (Albers and Klaas-Wissing, 2012). However, only a few studies of vertical alliances have pointed to the need for alliance transformation over time by referring to a firm's specific strategic (Fawcett et al, 2008) or operational capabilities (Bhatnagar and Viswanathan, 2000;Tate, 1996) of a firm.…”
Section: Consideration Of Alliance Dynamicsmentioning
confidence: 99%
“…• A strategic alliance is a CTN based on a long-term partnership and contractual agreements among companies [7]. For example, transport alliances might be formed by a group of small carriers to achieve economies of scale through serving transport demands from many small shippers or a few large shippers [23]. The formation of transport alliances requires making strategic decisions (e.g., partner selection), tactical decisions (e.g., cost and profit sharing), and operational decisions (e.g., collaborative vehicle routing and order sharing decisions).…”
Section: Overview Of Horizontal Collaboration In Freight Transportmentioning
confidence: 99%
“…Multiple studies showed that whenever resources are financed by partners, this ensures the commitment and support of the partners to make the CTN successful [10,52]. In large alliances, transport resources and assets are owned by partners while CDSSs, marketing, central management costs are financed by profits or transactional fees from the daily business in the CTN [23]. For example, the leading CTN 'Transplace' was founded in 2000 by six large freight carriers, each of which contributed $5 million in the funding of the CTN [33].…”
Section: Key Resourcesmentioning
confidence: 99%
See 1 more Smart Citation